(untitled) (Swiss Medical Weekly, 2013)
BACKGROUND: In 2004, complementary and alternative medicine (CAM) was offered by physicians in one-third of Swiss hospitals. Since then, CAM health policy has changed considerably. This study aimed to describe the present supply and use of CAM in hospitals in the French-speaking part of Switzerland, and to explore qualitatively the characteristics of this offer. METHODS: Between June 2011 and March 2012, a short questionnaire was sent to the medical directors of hospitals (n = 46), asking them whether CAM was offered, where and by whom. Then, a semi-directive interview was conducted with ten CAM therapists. RESULTS: Among 37 responses (return rate 80%), 19 medical directors indicated that their hospital offered at least one CAM and 18 reported that they did not. Acupuncture was the most frequently available CAM, followed by manual therapies, osteopathy and aromatherapy. The disciplines that offered CAM most frequently were rehabilitation, gynaecology and obstetrics, palliative care, psychiatry, and anaesthetics. In eight out of ten interviews, it appeared that the procedures for introducing a CAM in the hospital were not tightly supervised by the hospital and were mainly based on the goodwill of the therapists, rather than clinical/scientific evidence. CONCLUSION: The number of hospitals offering CAM in the French-speaking part of Switzerland seemed to have risen since 2004. The selection of a CAM to be offered in a hospital should be based on the same procedure of evaluation and validation as conventional therapy, and if the safety and efficiency of the CAM is evidence-based, it should receive the same resources as a conventional therapy.